(untitled) (LACCEI, 2024)
In the fields of computer science and electronics, the wide variety of tools and resources available for artificial intelligence and robotics are aimed at people with a certain level of expertise, so it is difficult for students to enter these fields without receiving help from specialists. Considering the above, this project proposes a didactic and affordable development environment for graphical programming based on nodes and a robot controlled by Raspberry Pi. The software architecture was made in Python with the support of graphic resources that allow the integration of libraries for signal processing, remote connection and artificial intelligence under the functional programming paradigm for the translation of instructions that are executed remotely in the robot controller. The result obtained was a friendly and intuitive programming environment that provides artificial intelligence functions to a multimodal robotic system controlled by Raspberry Pi.